Health Care Access for Latino Mixed-Status Families: Barriers, Strategies, and Implications for Reform. (December 2014) - Castañeda, Heide; Melo, Milena Andrea
There are approximately 2.3 million mixed-status families in the United States, containing varied combinations of citizens, permanent legal residents, undocumented immigrants, and individuals in legal limbo. These families offer an opportunity to examine the functioning of the contemporary state and its penetration at the household level. For many Latino youth, experiences are framed not only by their own but other family members' legal status. This article reports on health care seeking experiences of mixed-status families in the Lower Rio Grande Valley of South Texas and the impact of the recent health care reform (Affordable Care Act). We utilized qualitative ethnographic methods including 55 semistructured interviews with mixed-status families and 43 interviews with health care providers, caseworkers, and public health officials. Results indicate that changes accompanying the reform directly and indirectly affect mixed-status households' ability to access care. We describe strategies in times of illness, including those unique to border communities. We conclude that, for successful implementation of policies associated with health care reform, broader issues related to immigration status must be addressed, especially anxieties regarding future chances of regularization. These uniquely affect mixed-status families, create a ripple effect on all household members, and result in unintended consequences for U.S. citizen children. Implications point to the need for a pathway to citizenship for parents as a basic step in improving well-being of children.